Anti-inflammatory tetraquinane diterpenoids from a Crinipellis species. Issue 2 (15th January 2017) - Rohr, Markus; Oleinikov, Katharina; Jung, Mathias; Sandjo, Louis P.; Opatz, Till; Erkel, Gerhard
Graphical abstract: Abstract: The small pro-inflammatory 10 kDa chemokine CXCL10 (Interferon-inducible protein 10, IP-10) plays an important role in mediating immune responses through the activation and recruitment of leukocytes such as T cells, eosinophils, monocytes and NK cells to the sites of inflammation. Elevated levels of CXCL10 have been associated with chronic inflammatory and infectious diseases and therefore CXCL10 represents an attractive target for the development of new anti-inflammatory drugs. In a search for anti-inflammatory compounds from fungi inhibiting the inducible CXCL10 promoter activity, four new tetraquinane diterpenoids, crinipellin E (1 ), crinipellin F (2 ), crinipellin G (3 ) and crinipellin H (4 ) were isolated from fermentations of a Crinipellis species. The structures of the compounds were elucidated by a combination of one- and two-dimensional NMR spectroscopy and mass spectrometry. Compounds1, 2, and3 inhibited the LPS/IFN-γ induced CXCL10 promoter activity in transiently transfected human MonoMac6 cells in a dose-dependent manner with IC50 values of 15 μM, 1.5 μM, and 3.15 μM respectively, whereas compound4 was devoid of any biological activity. Moreover, compounds1, 2 and3 reduced mRNA levels and synthesis of pro-inflammatory mediators such as cytokines and chemokines in LPS/IFN-γ stimulated MonoMac6 cells.